THE USE OF CRITICAL REVIEW TO IMPROVE STUDENTS’ SKILL IN WRITING ESSAY TEXT - DESTIA HERLISYA; YOHANA PUSPITA DEWI; PURNA WIRATNO (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2025)
Today's students are familiar with technology, this makes their desire to write less. They are not taught to get used to writing something, they are used to typing something improperly without the rules of language use and correct spelling. Whereas, writing is a standard passive skill that students must at least master considering the demands that they must always write, whether it is daily assignments, writing proposals, journals and even theses. To improve students' English writing skills, researchers used critical review as one of the learning methods in the classroom. Critical review requires students to understand the details of the text, including the arguments, evidence, and conclusions presented. By reviewing something critically, students find it easier to express their thoughts in writing. This research is a classroom action research that has 2 cycles, the object of this research is English education students in semester 4 at STKIP PGRI Bandar Lampung. The results show that there is an increase in the average score of students' writing skill, and there is also an increase in student learning activities in the classroom. Keywords: Action research, Critical review, Writing Essay,